Cross-Culture Adaptation and Validation of the Indonesian Version of the Feeding Cues Follow-up Form (FCF-UF) on NICU Nurses - Dewi Irianti; Dessie Wanda; Fajar Tri Waluyanti; Mega Hasanul Huda (An Idea Health Journal, 2026)
Background: Premature infants often experience difficulties in oral feeding due to neurological immaturity and poor coordination of sucking, swallowing, and breathing. These challenges may delay the transition to full oral feeding and prolong hospitalization in neonatal intensive care units (NICUs). The Feeding Cues Follow-Up Form (FCF-UF) is designed to objectively assess feeding cues in premature infants; however, it has not been adapted for use in the Indonesian context. Methods: This cross-sectional study aimed to adapt and evaluate the psychometric properties of the Indonesian version of the FCF-UF. Data were collected from 266 NICU nurses working in several hospitals in Indonesia between June and August 2025. The cross-cultural adaptation process followed seven stages. Internal consistency was assessed using Cronbach’s alpha, and test-retest reliability was evaluated using the Intraclass Correlation Coefficient (ICC). Construct validity was examined through Confirmatory Factor Analysis (CFA), and known-group comparisons were conducted to explore differences in instrument scores across respondent characteristics. Result: The Indonesian version of the FCF-UF demonstrated excellent internal consistency (Cronbach’s alpha = 0.922) and high test-retest reliability (ICC = 0.99). CFA supported a one-factor structure with very good model fit (χ²/df = 0.87; RMSEA = 0.000; CFI = 1.000; TLI = 1.001), with strong factor loadings across all items. Known-group comparison showed that pediatric nurse specialists scored significantly higher than nurses with a bachelor’s degree (p= 0.001). Conclusion: The findings indicate that the Indonesian version of the FCF-UF is a reliable and valid instrument for assessing feeding cues in premature infants. This tool may assist NICU nurses in implementing cue-based care and supporting the transition to oral feeding.